The Impact of Sociodemographic Factors on Inpatient Palliative Care Consultation for Patients with Brain and Spine Metastases. (16th November 2020) - Price, Meghan; Howell, Elizabeth P; Dalton, Tara; Ramirez, Luis; Williamson, Theresa; Painter, Brice; Check, Devon; Kamal, Arif; Goodwin, C. Rory
Abstract: INTRODUCTION: Patients diagnosed with brain and spine metastases (BSM) face high symptom burden and complex clinical decision-making. Through expertise in pain and symptom management, facilitation of end-of-life planning, and caregiver support, specialty Palliative Care (PC) can meaningfully improve the quality of life of these patients. METHODS: We examined the rates of PC consults in a cohort of BSM inpatients admitted to three tertiary medical centers: one major academic center and two smaller affiliate centers from 2016 to 2019. Using the electronic health record, we identified patients using a combination of ICD-9 and -10 codes and surgical provider lists to aggregate brain metastases patient cohorts. Patient demographics, surgical status, and readmission data were collected. PC utilization was assessed by flagging encounters for which an inpatient consult to PC was placed. Statistical analyses including student t tests for continuous variables, chi square test for categorical variables, and Kaplan meier curves for survival data were performed. RESULTS: 2608 total discharges were analyzed, with 2397 brain metastasis (BM) and 301 spine metastasis (SM) discharges. Average rate of inpatient PC consultation over the 3.5-year study period was 13.6% for BM patients and 11.0% for SM patients. Rates of PC utilization differed significantly by patient race (11.6% in white vs. 17.0% in non-white patients, P = .02). Additionally, patients who received surgery had significantly lower rates of PC consultation in both BM (3.5% vs 15.6%, P < .001) and SM (5.5% vs 14.1% P < .001) cohorts. Utilization rates were also found to vary by practice setting and discharging service. CONCLUSION: Despite their high symptom burden and low overall survival, BSM patients have low rates of inpatient PC consultation. Utilization appears to vary by patient demographics, surgical status, discharging service and practice setting. These single-institution patterns may provide a microcosm for national trends at similar institutions, and further work is needed to identify the specific barriers to optimally utilizing specialty PC in this population.